Assessing Hand Muscle Structural Modifications in Chronic Stroke - Zong, Ya; Shin, Henry H.; Wang, Ying-Chih; Li, Sheng; Zhou, Ping; Li, Xiaoyan (Frontiers in Neurology, 2018)
The purpose of the study is to assess post-stroke muscle structural alterations by examining muscular electrical conductivity and inherent electrophysiological properties. In particular, muscle impedance and compound muscle action potentials (CMAP) were measured from the hypothenar muscle bilaterally using the electrical impedance myography (EIM) and the electrophysiological techniques, respectively. Significant changes of muscle impedance were observed in the paretic muscle compared with the contralateral side (resistance: paretic: 27.54 ± 0.97 Ohm, contralateral: 25.46 ± 0.91 Ohm, p< 0.05; phase angle: paretic: 8.81 ± 0.61°, contralateral: 10.79 ± 0.69°, p<0.05). In addition, impedance changes correlate moderately with the CMAP amplitude in the paretic hand (phase angle: r=0.66, p<0.05; reactance: r=0.58, p<0.05). The study discloses significant muscle rearrangements as a result of fiber loss or atrophy, fat infiltration or impaired membrane integrity in chronic stroke.